2019
DOI: 10.1177/0309524x19849845
|View full text |Cite
|
Sign up to set email alerts
|

Development and performance testing of a small, multi-bladed wind turbine

Abstract: This article presents selected results from the development process of a small, prototype multi-bladed wind turbine designed to replace the American western-style, wind-driven water pumps still encountered in the Maltese rural landscape. The main focus of this article is on the rotor design, fabrication and system assembly, as well as on the results of the first open field tests. While the new design proves that the new machine is capable of aesthetically representing the windmills of old, preliminary findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Equation (9) proposed by Lanzafame and Messina 32 was utilized for a#. Unlike the commonly used form in Manwell et al 18 which is a function of both F and u, equation ( 9) depends solely on a.…”
Section: Bem Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (9) proposed by Lanzafame and Messina 32 was utilized for a#. Unlike the commonly used form in Manwell et al 18 which is a function of both F and u, equation ( 9) depends solely on a.…”
Section: Bem Methodsmentioning
confidence: 99%
“…In the experiments, optimum performance of a 0.5-m diameter turbine was achieved with a 3-blade, low design TSR rotor. Sant et al 9 reported on the design, installation, and power generation test results of a 9-blade turbine with a 3.4-m diameter to replace the American wind-driven water pump. The blades were shaped using the Eppler 197 airfoil profile.…”
Section: Introductionmentioning
confidence: 99%
“…The windmill used here was developed by Singh 12 as a model of Wegereef's and a comparison of its thrust, power, and torque is given in John 13 . Other recent windmill studies include Sarkis and Pinilla 14 and Sant et al 15 who both considered non‐standard airfoil profiles for the blades.…”
Section: Introductionmentioning
confidence: 99%